2018
DOI: 10.21890/ijres.383184
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition, Positioning and Emotions in Mathematical Activities

Abstract: Researchers of mathematics education have been paying attention to the affective aspect of learning mathematics for more than one decade. Different theoretical frameworks have been suggested to analyze this aspect, where we utilize in the present research the discursive framework of Evans, Morgan and Tsatsaroni. This framework enables to link students" positions to their emotions. Here, we add to this relationship the metacognition variable, where we study how the added variable affects students" positioning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
3
18
0
2
Order By: Relevance
“…Flavel described metacognitive knowledge as individuals related to their own cognitive activity or everything related to it [4], [5]. However, along with the rapid research on metacognitive, various experts provide new definitions as a refinement of the original idea, for example, Daher, Anabousy, and Jabarin [6] define metacognition as cognition about cognition or knowledge about knowledge. In line with the definition from Van De Bogart, Dounas-Frazer, Lewandowski, & Stetzer [7] interpret metacognition as thinking about one's thoughts.…”
Section: Introductionmentioning
confidence: 99%
“…Flavel described metacognitive knowledge as individuals related to their own cognitive activity or everything related to it [4], [5]. However, along with the rapid research on metacognitive, various experts provide new definitions as a refinement of the original idea, for example, Daher, Anabousy, and Jabarin [6] define metacognition as cognition about cognition or knowledge about knowledge. In line with the definition from Van De Bogart, Dounas-Frazer, Lewandowski, & Stetzer [7] interpret metacognition as thinking about one's thoughts.…”
Section: Introductionmentioning
confidence: 99%
“…First, in mastery of mathematics concept and second is about student's thinking skills. Reviewed articles showed that implementation of metacognitive learning strategies by organizing certain activities likes Problem Based Learning, Project Work, Discussion, Game, etc, is mostly effective to students performance and understanding (e.g; Daher, Anabousy, & Jabarin, 2018;Smith & Mancy, 2018;Suriyon, Inprasitha, & Sangaroon, 2013). It means, student learning is greatly enhanced when the student's level of prior knowledge is made visible.…”
Section: What Is the Impact Of Learning Activities As The Interventiomentioning
confidence: 99%
“…The phase of analysis is the phase that is most closely related to the operational design of intervention. Researchers such as Menz and Cindy Xin (2016), Du Toit & Du Toit (2013), Tony Karnain et al (2014), Daher, Anabousy, and Jabarin (2018), Smith and Mancy (2018), Hasbullah (2015) Cera, Mancini and Antionetti (2013) have reported that implementing this phase to produce the activities based on MLS.…”
Section: Which Aspect(s) Is Most Closely Related To the Operational Dmentioning
confidence: 99%
See 2 more Smart Citations